The Influence of Student Interest on Student Learning Outcomes in Science Subjects - M. Dwi Wiwik Ernawati*; Sudarmin Sudarmin; Asrial Asrial; Haryanto Haryanto; Aulia Sanova; Dwi Agus Kurniawan; Miftahul Zannah Azzahra (Jurnal Pendidikan Sains Indonesia, 2022)
The formulation of the problem in this study is how the comparison and influence of interest in learning on science learning outcomes of students in SMP 22 Batanghari and SMP 1 Muaro Jambi. The purpose of this research is to find out how the comparison and influence of interest in learning on science learning outcomes of students at SMP 22 Batanghari and SMP 1 Muaro Jambi. This study also serves to see how important student interest in learning is to student learning outcomes in science subjects at the junior high school level. This study uses a mix method research with explanatory design and the data analysis technique used is random sampling. Based on the t-test of student interest in learning and student learning outcomes obtained a significance value of 0.05 so it can be concluded that there is a difference between student interest in learning and student learning outcomes in science subjects at SMP 22 Batanghari and SMP 1 Muaro Jambi. Based on the regression test of student interest in learning and student learning outcomes obtained a significance value of 0.05 so it can be concluded that there is an influence between student interest in learning and student learning outcomes in science subjects at SMP 22 Batanghari and SMP 1 Muaro Jambi